Two for one: Viral helicases as an ideal target for HIV and HCV co-infection. (July 2018) - Anwar, Muhammad Faraz; Zarina, Shamshad; Ali, Syed; Abidi, Syed Hani
Abstract: Helicase enzyme is responsible for the unwinding of complementary nucleic acid strands, which is one of the preliminary steps in DNA replication. They are crucial for replication of an organism, including viruses. HCV and HIV are two clinically significant pathogens, responsible for millions of infections and deaths worldwide. Due to similar transmission routes, these viruses can establish co-infection in an individual. Individually, these infections are difficult to treat, however, in case of co-infection, the treatment becomes more difficult. Additionally, these viruses accumulate mutation in response to drug therapy that renders the treatment ineffective. HCV and HIV both encode enzyme containing helicase activity. The viral-encoded helicase plays a significant role in HIV and HCV life cycle. Here we propose viral helicases as an ideal single-hit target that can inhibit HIV and HCV co-infection. We also hypothesize that search for natural analogs sharing basic ring structure with a class of helicase inhibitors called fluoroquinolones can yield natural agents with superior antiviral (anti-helicase) activity with lower toxicity index. The fluoroquinolones and their analogs are currently not part of any antiviral regimens. Our proposal is to include fluoroquinolones-derived natural analogs as a conjugate therapy along with main regimens available against HCV and HIV co-infection.